Mengembangkan Teknik Reportase Investigasi Untuk Mendukung Transparansi Publik - Kusuma, Adhi; Yanti , Siti Mustika; Kurnia , Revy; Kamiliya , Nur Aufa (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
Investigative reporting techniques are a crucial approach in journalism that aims to uncover hidden facts and deliver relevant information to the public. In the era of democratization and information openness, investigative reporting plays a vital role in supporting public transparency. This article aims to develop more effective investigative reporting techniques to enhance the accountability of government, institutions, and the private sector. The research method employed includes literature review and interviews with media practitioners and investigative journalists, as well as the analysis of various successful investigative reporting case studies. The findings indicate that new techniques in data collection, the use of digital technology, and collaboration among media outlets can improve the quality of investigative reporting. The author also recommends more intensive training for journalists to identify credible information sources and manage data effectively. Thus, the development of these techniques can strengthen the role of the media in promoting transparency and public accountability across various sectors.